Aspects of the Performative in Medieval Culture - Suerbaum, Almut; Gragnolati, Manuele (Trends in Medieval Philology, 2010)
The volume assesses performative structures within a variety of medieval forms of textuality, from vernacular literature to records of parliamentary proceedings, from prayer books to musical composition. Three issues are central to the volume:the role of ritual speech acts the way in which authorship can be seen as created within medieval texts rather than as a given category finally, phenomena of voice, created and situated between citation and repetition, especially in forms which appropriate and transform literary tradition. The volume encompasses articles by historians and musicologists as well as literary scholars.